IL-5, IL-8 and MMP -9 levels in exhaled breath condensate of atopic and nonatopic asthmatic children. Issue 6 (June 2015) - Turkeli, Ahmet; Yilmaz, Ozge; Taneli, Fatma; Horasan, Gonul Dinc; Kanik, Esra Toprak; Kizilkaya, Metehan; Gozukara, Ceyhun; Yuksel, Hasan
Summary: Rationale: Asthma is a heterogeneous disease, and a great majority of pediatric patients with asthma demonstrate atopic characteristics and develop a Th2 type cytokine response. Nonatopic asthma, on the other hand, is seen more rarely. Methods: In this study, levels of IL-5, IL-8 and MMP-9 were measured in exhaled breath condensate (EBC) of the subjects to demonstrate the extent of tissue damage as well as eosinophilic and neutrophilic inflammation in children with atopic and nonatopic asthma. A total of 37 children with atopic asthma and 37 children with nonatopic asthma were enrolled in the study. Patients who exhibited protease positive aeroallergen (House dust mite, mould mix, olea, grass mix) sensitivity in allergen skin prick test were included in the atopic asthma group. To evaluate the EBC, the fluid content of the breath was collected by having the patients exhale into an EBC device, after which the IL-5, IL-8 and MMP-9 levels were assayed using the ELISA method. Results: The atopic asthmatics exhibited significantly higher IL-5 levels in their EBC samples than the nonatopic asthmatics (0.271 [0.198–0.489] pg/ml and 0.198 [0.125–0.344] pg/ml, respectively, p = 0.04), while no significant differences were observed in the levels of IL-8 and MMP-9 in the EBC samples of the atopic and nonatopic asthmatics. Conclusions: IL-5 levels, as a marker of eosinophilic inflammation, were demonstrated to be higher in the children with atopic asthma when compared to those with nonatopic asthma in EBC. The fact that no significant difference was apparent in the IL-8 levels between the groups suggests that it is the severity of the disease rather than the atopic state that plays an important role in IL-8 levels. Since no difference was recorded between the groups in terms of MMP-9 levels, lung damage in asthma sufferers seems to develop independent of atopia.